Application of Nanoemulsion of Balanite aegyptiaca Seed Kernel Extract on Plant Parasitic Nematodes of Okra and its effect on Okra (Abelmoschus esculentus) growth and yield parameters in Adamawa State, Nigeria - J, Akwayamai P.; Jada, M. Y.; O, Pheobe A.; F, Timon (African Journal of Sciences and Traditional Medicine, 2025)
Okra is known to be attacked by many pests; the status of plant parasitic nematodes and its management on okra is not known in Adamawa state. This study assessed the use and application of nanoemulsion of Balanites aegyptiaca seed kernel extract on plant parasitic nematodes in okra-cultivated soils in Adamawa State and its effect on the growth and yield parameters. The nanoemulsion was obtained from the Department of Crop Protection, Modibbo Adama University Yola (MAU), and applied at rates of 1.2 ml/plot (3 L/ha), 2.4 ml/plot (6 L/ha), 3.6 ml/plot (9 L/ha), and 4.8 ml/plot (12 L/ha). Carbofuran at 1.6 g/plot (4 kg/ha) served as the positive control, while zero application was the negative control. The experiments were laid in a Randomized Complete Block Design (RCBD) at Adamawa State University (ADSU) Mubi, and MAU Yola. Agronomic parameters such as plant height, number of branches, stem girth, fruit length, fruit diameter, root length, and total yield weight were evaluated. Data were analyzed using ANOVA, with mean separation by DMRT at 0.05% significance level. The result shows the application of nanoemulsion of Balanites aegyptiaca seed kernel extracts at 4.8 ml/plot (12 L/ha) significantly enhanced growth parameters such as plant height at 6 and 8 WAE improved (19.58, 29.42), stem girth (12.88, 18.83) and number of branches (6.57, 16.32) and with the highest yield recorded at 2245.25 kg (2.2 tons/ha) compared to 944.83 kg (0.9 tons/ha) in the control. It is recommended that Farmers need to adopt the management practices of plant parasitic nematode on okra cultivated field with application at the rate of 9 L/ha and 12 L /ha as it gave the promising result.